From Integration to Marginalization: The Influence of Assimilation Policies on Benteng Chinese Society 1966-1997 - Nuraeni, Nuraeni; Fauzan, Rikza; Nurhasanah, Ana (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The aims of this research are: To analyze the influence of New Order policies on the Chinese Benteng community in Tangerang City in 1966-1997. The research method used is the historical method which consists of heuristics, criticism, interpretation and historiography. The results of the study revealed that as a result of this policy, the Chinese Benteng community in Tangerang City, who were peranakan Chinese in Indonesia, were also affected. In the political field they are not allowed to be elected, they have difficulty obtaining an identity due to the difficulty in obtaining an SBKRI, in the social field they change their Chinese name to an Indonesian name, in the economic field the Chinese Benteng community has difficulty getting a job, in the cultural sector there are traditions that are generally performed in public being banned and carried out secretly in the Temple, and in the religious field some of the Benteng Chinese people who adhere to the Confucian religion are not recognized as religious.